Hepatitis E genotype 3 genome: A comprehensive analysis of entropy, motif conservation, relevant mutations, and clade-associated polymorphisms - Muñoz-Chimeno, Milagros; Rodriguez-Paredes, Vanessa; García-Lugo, Maira Alejandra; Avellon, Ana (Frontiers in Microbiology, 2022)
Hepatitis E virus genotype 3 (HEV-3) is an EU/EEA emergent zoonosis. HEV-3 clades/subtypes have been described. Its genome contains ORF1, encodes nonstructural proteins for virus replication, ORF2, the capsid protein, and ORF3, considered to be a multifunctional protein involved in virion pathogenesis. The study aims with respect to HEV-3 are to: 1) calculate genome entropy (excluding hypervariable region); 2) analyze the described motifs/mutations; 3) characterize clade/subtype genome polymorphisms. A total of 705 sequences from GenBank database were used. The highest entropies were identified in zoonotic genotypes (HEV-3 and HEV-4) with respect to HEV-1 in X domain, RdRp, ORF2 and ORF3. There were statistically significant differences in the entropy between proteins, protease and ORF3 being the most variable and Y domain being the most conserved. Methyltransferase and Y domain motifs were completely conserved. By contrast, protease essential H581 and catalytic dyad exhibited amino acid changes in 1.8% and 0.4% of sequences, respectively. Several amino acids of X domain were associated with clades. We found sequences with mutations in all helicase motifs except number IV. Helicase mutations related to increased virulence and/or fulminant hepatitis were frequent, being the 1110 residue a typical HEV-3e and HEV-3f-A2 polymorphism. RdRp motifs III, V, VII also had high mutation rates. Motif III included residues that are polymorphisms of HEV-3e (F1449) and HEV-3m (D1451). RdRp ribavirin resistance mutations were frequent, mainly 1479I (67.4%, 100% in HEV-3efglmk) and 1634R/K (10.0%, almost 100% in HEV-3e). With respect to ORF2, 19/27 neutralization epitopes had mutations. S80 residue in ORF3 presented mutations in 3.5% of cases. Amino acids in ORF3-PSAP motif had high substitution rates, being more frequent in the first PSAP (44.8%) than in the second (1.5%). This is the first comprehensive HEV-3 genome analysis. It aims to improve our knowledge of the genome, and to establish the basis for a future genotype-to-phenotype analysis, given that viral features associated with severity have not been explored in depth. Our results demonstrate there are important genetic differences in the studied genomes that sometimes affect viral structures of known significance, and constitute clade/subtype polymorphisms that may affect the clinical course or treatment efficacy.